OsDREB2B, an AP2/ERF transcription factor, negatively regulates plant height by conferring GA metabolism in rice - Ma, Ziming; Jin, Yong-Mei; Wu, Tao; Hu, Lanjuan; Zhang, Ying; Jiang, Wenzhu; Du, Xinglin (Frontiers in Plant Science, 2022)
The AP2/ERF family is a large group of plant-specific transcription factors that play an important role in many biological processes, such as growth, development, and abiotic stress responses. OsDREB2B, a dehydration responsive factor (DRE/CRT) in the DREB subgroup of the AP2/ERF family, is associated with abiotic stress responses, such as cold, drought, salt, and heat stress, in Arabidopsis or rice. However, its role in regulating plant growth and development in rice is unclear. In this study, we reported a new function of OsDREB2B, which negatively regulates plant height in rice. OsDREB2B-overexpressing rice harboring dwarf phenotypes was obtained from our transcription factor library. Compared with wild type (WT), OsDREB2B-overexpressing (OE) lines exhibited reduced plant height, internode length and thickness, and seed size, as well as grain yield decline, while the knockout mutants developed by CRISPR/Cas9 technology exhibited similar phenotypes. Spatial expression analysis revealed that OsDREB2B was highly expressed in the leaf sheaths. Under exogenous GA3 application, OsDREB2B expression was induced, and the length of the second leaf sheath of the OsDREB2B-OE lines recovered to that of the WT. OsDREB2B localized to the nucleus of the rice protoplast acted as a transcription activator and upregulated OsAP2-39 by directly binding to its promoter. OsDREB2B-OE lines reduced endogenous bioactive GA levels by downregulating seven GA biosynthesis genes and upregulating eight GA deactivation genes but not GA signaling genes. The yeast two-hybrid assay and bimolecular fluorescence complementation assay showed that OsDREB2B interacted with OsWRKY21. In summary, our study suggests that OsDREB2B plays a negative role in rice growth and development by regulating GA metabolic gene expression, which is mediated by OsAP2-39 and OsWRKY21, thereby reducing GA content and rice plant height.